KOORDINASI PEMERINTAH DESA DENGAN PIHAK TERKAIT DATA PENERIMA PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) PADA MASA PANDEMI COVID-19 DI DESA PULAU KECIL KECAMATAN RETEH KABUPATEN INDRAGIRI HILIR TAHUN 2020-2021 - Putri Dwi Lestari; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Village Fund Direct Cash Assistance Program aims to reduce the burden on the community, especially the rural poor who are affected by the Covid-19 pandemic, so as to prevent a decline in the welfare level of rural communities. Because the BLT-DD program helps the economy of rural communities who experienced an economic downturn during the Covid-19 pandemic so that they can still meet their basic daily needs. The target of BLT-DD is intended for non-PKH or BPNT poor families, and poor families who are recorded in the DTKS and not recorded. As in Pulau Kecil Village, there was a wrong target due to the village government's lack of wisdom in responding to this. The purpose of this study was to find out how the Village Government coordinated with parties related to BLT-DD beneficiary data and obstacles in village government coordination regarding the BLT-DD program in Pulau Kecil Village.The theory used is the theory of government coordination by Inu Kencana Syafiie regarding the elements of coordination, namely regulation, synchronization, common goals and common interests. The research method used is descriptive qualitative to get a clear picture of the management carried out related to the coordination of the Village Fund Direct Cash Assistance program. Data collection techniques were carried out by means of interviews and documentation. The results of this study are that the coordination of the Village Government with parties related to BLT-DD program beneficiary data in 2020 has not been maximized, this can be seen from the coordination of the Village Government itself with the RT as the party carrying out the data collection where communication is still not good, this This has become an inhibiting factor in coordinating village governments in implementing the BLT-DD program due to the obstruction to movement due to the high spike in cases of the Covid-19 pandemic. Whereas in 2021, the village government will only continue the program according to the beneficiary data available in 2020. Keywords: Coordination, Direct Village Fund Cash Assistance (BLT-DD)